Potensi Ekonomi Pemanfaatan Dan Pengelolaan Sekam Padi Sebagai Bioenergi: Studi Kasus Agro-Energi Kabupaten Cianjur: Economic Potential and Management of Rice Husks Utilization as Agro-Energy in Cianjur Regency - Panca Sandika; Akhmad Fauzi; Meilanie Buitenzorgy (Indonesian Journal of Agricultural Resource and Environmental Economics, 2026)
Indonesia faces dual challenges in energy security and agricultural waste management. Rice husk offers significant bioenergy potential, yet its utilization is constrained by economic, social, and policy uncertainties. This study aims to analyze the economic potential of utilizing rice husks as bioenergy, analyze stakeholder perspectives, positions, and power regarding the potential use of rice husk bioenergy to map potential conflicts and align strategies. and estimate the probability of future policy scenarios regarding the implementation of rice husk use as agricultural bioenergy in Cianjur Regency to formulate priority recommendations. A three-stage integrated framework of research method was employed: Extended Cost-Benefit Analysis (eCBA), Stakeholder Analysis (MACTOR), and Probabilistic Scenario Planning (SMIC-PROB). The eCBA results indicate quite high such as feasible in economics, with a Net Present Value (NPV) of IDR 965,2 billion and a Benefit-Cost Ratio of 2,04, driven by energy substitution and the circular value of ash fertilizer. MACTOR analysis identifies a strong coalition between the government and rice millers but highlights friction with investment agencies regarding licensing. Furthermore, SMIC-PROB analysis reveals that "Infrastructure Development" is the prime mover policy essential for success. The study concludes that rice husk bioenergy is a socio-economically viable circular investment, contingent upon prioritizing rural logistics infrastructure to unlock technological adoption Indonesia menghadapi tantangan ganda dalam ketahanan energi dan pengelolaan limbah pertanian. Sekam padi menawarkan potensi bioenergi yang signifikan, namun pemanfaatannya terkendala oleh ketidakpastian ekonomi, sosial, dan kebijakan. Penelitian ini bertujuan untuk menganalisis potensi ekonomi pemanfaatan sekam padi sebagai bioenergi; menganalisis pandangan, posisi, dan kekuatan pemangku kepentingan dalam melihat potensi penggunaan bioenergi sekam padi untuk memetakan potensi konflik dan koalisi strategis; dan mengestimasi probabilitas skenario kebijakan masa depan tentang implementasi penggunaan sekam padi sebagai bioenergi untuk merumuskan rekomendasi prioritas di Kabupaten CIanjur. Kerangka kerja terintegrasi tiga tahap metode penelitian yang digunakan: Extended Cost-Benefit Analysis (eCBA), Stakeholder Analysis (MACTOR), dan Probabilistic Scenario Planning (SMIC-PROB). Hasil eCBA menunjukkan kelayakan ekonomi yang cukup tinggi, dengan Net Present Value (NPV) sebesar Rp 965,2 miliar dan Benefit-Cost Ratio 2,04, yang didorong oleh substitusi energi dan nilai ekonomi sirkular dari pupuk abu. Analisis MACTOR mengidentifikasi koalisi kuat antara pemerintah dan penggilingan padi, namun menyoroti adanya hambatan dengan lembaga investasi terkait perizinan. Selanjutnya, analisis SMIC-PROB mengungkapkan bahwa "Pembangunan Infrastruktur" merupakan kebijakan penggerak utama yang esensial bagi keberhasilan program. Studi ini menyimpulkan bahwa bioenergi sekam padi merupakan investasi ekonomi sirkular yang layak secara sosio-ekonomi, namun keberhasilannya bergantung pada prioritas pembangunan infrastruktur logistik pedesaan untuk mendukung adopsi teknologi.